Short-term effects of light and heavy load interventions on service velocity and precision in elite young tennis players - Ferrauti, A.; Bastiaens, K. (British Journal of Sports Medicine, 2007)
Objective: This study was conducted to investigate the acute effects of a complex throwing intervention set-up, with light or heavy loads, on the service velocity of elite junior tennis players.